Outcome of trans-catheter edge-to-edge mitral valve repair in patients with severe left ventricular dilatation. (3rd October 2022) - Raphael, R; Makmal, N M; Silbermintz, N S; Faierstein, K F; Moeller, C M; Canetti, M C; Maor, E M; Kuperstein, R F; Hai, I H; Butnaru, A B; Oren, D O; Guetta, V G; et al.
Abstract: Introduction: The COAPT trial established the benefit of trans-catheter edge-to-edge mitral valve repair (TEER) for patients with symptomatic secondary mitral regurgitation (MR). However, patients with severe LV dilatation were excluded from this study. Furthermore, disproportionate LV dilatation has been proposed as a possible explanation for the lack of benefit in the Mitra-FR trial. Purpose: The purpose of this study was to evaluate the safety and efficacy of TEER in patients with severe LV dilatation. Methods: We categorized patients with secondary MR and severe LV dilatation based on LVEDD/BSA ratio using a cut-off of >3.6cm/m 2 in men and >3.7cm/m 2 in women. Results: We included 121 patients, 25 patients with severe LV dilatation (S) and 96 without (NS). Mean LVEDD was 68.9±6.6mm in the S group vs 58.5±6.5mm in the NS group. Compared to the NS patients, patients with severe LV dilatation were younger (age 69±10 vs 74±10 years), had lower LVEF (37+14% vs 29+7%), and lower GFR (44±21 vs 55±26). There was no significant difference in MR grade (3.3 vs 3.3), however the S group had numerically greater EROA (EROA 0.45 vs 0.35). No significant differences were noted in NYHA class (2.8 vs 2.76) or SPAP (59mmHg for both). Peri-procedural adverse events were rare in both groups. One peri-procedural death was noted, 2 patients underwent urgent dialysis, 1 had cardiogenic shock, and 2 had prolonged ventilation after the procedure, all of these occurred in the NS group. At 1-year follow-up, there was marked improvement in MR grade (2.4±1.4 vs 2.2±1.2 for S and NS respectively). Both groups had a small reduction in LVEDD of about 3mm. Patients in the S group had improved GFR at 1-year follow-up (44±21 to 51±32). No differences were noted in 1, 2, or 5 year mortality between groups (Figures). Conclusion: Trans-catheter edge-to-edge mitral valve repair in patients with severe LV dilatation is safe and seems to provide similar short-and long-term outcomes compared to patients with less severe dilatation. Further studies are needed to establish the efficacy of TEER for these patients. Funding Acknowledgement: Type of funding sources: None.